Relationship between Nutritional Knowledge and Eating Habits with Adolescent Nutritional Status at MTS Persis Sukabumi City. - septica, qorry qorry; lestari, ranti ranti (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2024)
Adolescence is a very important period in the process of human growth and development, the condition of adulthood is largely determined by the state of nutrition and health in adolescence. Nutritional problems that arise in adolescence are caused by a lack of knowledge and poor eating patterns causing an imbalance between consumption and recommended nutritional adequacy. The purpose of this study was to determine the relationship between nutritional knowledge and eating habits with the adolescent nutritional status. This study used a correlational with a cross-sectional study design. The research was conducted in March 2022 at MTS Persis Sukabumi City. The population of this study was all teenagers 13-15 years, totaling 57 people and the sampling technique is total sampling. Data were collected using a questionnaire which was then analyzed using the Chi-Square test. The results showed that there was a relationship between nutritional knowledge and the nutritional status of adolescent girls with a p-value of 0.001 <0.05. There is a relationship between diet and nutritional status with a p-value of 0.0014 <0.05. There is a relationship between nutritional knowledge and eating habits with adolescent nutritional status at MTS Persis Sukabumi City.